Biomarkers for Cognitive Dysfunction: An Evidence Based Exploratory Review and the Challenges Involved in Developing Biomarkers - Jerin James; Jamuna Rani; V. Sathyanarayanan (Recent Progress in Science and Technology Vol. 9, 2023)
As the population ages, the prevalence of cognitive dysfunction increases, making it a major public health concern. Biomarkers that can detect cognitive dysfunction early may provide a window for interventions that could delay or prevent its progression. This review article examines the current state of biomarker research for cognitive dysfunction, including structural and functional neuroimaging, cerebrospinal fluid biomarkers, and blood-based biomarkers. It discusses the strengths and limitations of each type of biomarker and highlights promising new areas of research. The article also discusses challenges in developing biomarkers for cognitive dysfunction, such as the lack of consensus on diagnostic criteria and the need for large, longitudinal studies. Overall, the review highlights the potential of biomarkers to improve the diagnosis and treatment of cognitive dysfunction and the need for continued research in this area.